Crossing between the Great Wall of China and the "Great" Trump Wall. Issue 1 (December 2017) - Yang, Mimi
Abstract Can a border wall really deter invaders and crossers alike, while defending, unifying, and maintaining the "purity" of the culture that it encircles? The first Chinese emperor Qin Shihuang (259-210 BC) and his successors in the following dynasties tried to achieve the purpose; the Great Wall of China testifies timelessly to such epic efforts. Have the Chinese rulers succeeded? The question has become increasingly daunting and unanswerable as history unfolds and evolves. Ironically, over more than two millennia, the piecemeal erection of the Great Wall has indeed sequenced a 'wall-DNA' in a cultural blueprint. Fast forwarding to the 21st century America, we find ourselves asking the same questions when President Trump vows to build a "great, great" wall, physical and impenetrable on the US-Mexico border. The Trump Wall is designed to stop Mexican illegal immigrants entering the US so that Americans' interests will be protected, English language will not be "contaminated", and American values will not be challenged. The Trump wall sets out to delineate what America is and thus attempts to "make America great again". In an intercultural engagement, this article decodes a wall-DNA in American culture, argues that the Trump wll is more of a mental construct than a physical one, and calls for a redefinition of a 21st century American cultural identity, in front of the Trump Wall.